Cold and hot region detectability and image quality enhancement in Tc99m SPECT by reduction of scattered gamma photons prior to detection - Shah, Sayed Inayatullah; Harun, Siti Zawani (Springer Netherlands, 2011)
Presence of scattered gamma photons in SPECT projection data degrades the image quality and limits the accuracy in quantification of radiopharmaceutical distribution. Therefore, it is imperative to remove the scattered gamma photons from SPECT data. In this work, a material filter technique, which absorbs some fraction of scattered gamma photons before they can reach the surface of gamma camera detector, was used. A new phantom provides similar cross sectional views of cold and hot regions insert, filled with water and Tc99m radioactivity distributed uniformly in the phantom was scanned. Philip ADAC Forte dual head gamma camera was used with LEHR collimator. Material filter (sheet) - Cu 0.127 mm and Al 0.2 mm thick - was attached (each separately) on the outer surface of the collimator and data were acquired without and with material filter(s). Filtered back projection technique was used with Butterworth filter selecting 0.35 cycles / cm cut-off frequency and order 5. Chang’s method was applied using 0.13/cm  value for attenuation correction. Images were visually inspected in order to observe the cold and hot region detectability. Contrast, SNR and standard deviation in the count density of uniform, cold and hot region images were measured. Results indicate an overall improvement in image uniformity, quality of cold and hot regions and detectability with both material filters in conjunction with Butterworth filter. In conclusion, material filters may improve image quality in clinical studies.